Internal migration in India : a case study of Bengal - Chattopadhyaya, Haraprasad (Calcutta : K.P. Bagchi & Co., 1987)
Study covers the period from the second half of 19th century to 1931.
Includes bibliographies and index.
Keywords: Migration, Internal -- India -- Bengal -- Case studies